Orchestrating performance of healthcare networks subjected to the compound events of natural disasters and pandemic - Emad M. Hassan (Nature Portfolio, 2021)
COVID-19 might occur together with other natural disasters but frameworks to quantify collective effects is lacking. Here, the authors investigated the readiness of a healthcare system in the face of wildfire during an epidemic by assuming the COVID-19 pandemic occurred around the same time with the Camp Fire case in Butte Country California 2018/2019.